Chronic recurrent sialadenitis of the submandibular gland, case report, and literature review - Jerez Robalino, James Philippe (2023)
Sialadenitis is defined as an inflammation of the major salivary glands and has multiple etiologies. this article reported the case of a 17-year-old girl treated in the Maxillofacial Surgery service of the “Hospital General la Perla”. The patient presents an increase in volume in the right submandibular region, she reports 5 months of evolution, 12 days of antibiotic/analgesic treatment, and persistent symptoms. The requested tomographic study shows an isodense that suggests increased volume at the right submandibular gland. Due to the correlation between clinical and imaging presentation, chronic sialadenitis is diagnosticated. The patient is prepared to go to the operating room to remove the affected gland. Under general anesthesia, submandibular access, and dissection the submandibulectomy was achieved. The suture by planes is with Vicryl 3-0 and Nylon 5-0. The controls conducted at 7 and 30 days indicate normal healing and evolution, without nervous alterations. That is why is important for the clinician to have complete knowledge of the anatomy and pathology so that he will perform this procedure successfully, reducing the possibility of post-treatment complications.